Risk factors for shoulder and elbow pain in youth baseball players - Matsuura, T.; Iwame, T.; Suzue, N.; Arisawa, K.; Sairyo, K. (The Physician and Sportsmedicine, 2017)
Objectives: This study sought to quantify the 1-year cumulative incidence of shoulder and elbow pain among youth baseball players and identify risk factors associated with the occurrence of shoulder and elbow pain.